2010
DOI: 10.1063/1.3484966
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete screening by epitaxial graphene on the Si face of 6H–SiC(0001)

Abstract: A biased scanning tunneling microscope (STM) tip is used to study the ability of carriers in graphene to screen external electrostatic fields by monitoring the effect of tunneling-junction width on the position of image potential-derived surface states. These states are unusually sensitive to local electric fields due to the STM tip in both single layer and bilayer epitaxial graphene. This is attributed to the incomplete screening of applied fields in epitaxial graphene on SiC(0001). Our observations imply tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…These graphene image potential levels have been predicted to exhibit a unique double Rydberg series, 36 and this has been confirmed experimentally 37 and exploited as a local transport probe of epitaxial graphene. 38 These levels are of potential interest because their weak binding leads to heightened sensitivity to the local electrostatics, thus opening the possibility for modulating electronic properties. This would, however, require tuning these levels to near the Fermi level, for instance, by endohedral doping of C 60 .…”
Section: Discussionmentioning
confidence: 99%
“…These graphene image potential levels have been predicted to exhibit a unique double Rydberg series, 36 and this has been confirmed experimentally 37 and exploited as a local transport probe of epitaxial graphene. 38 These levels are of potential interest because their weak binding leads to heightened sensitivity to the local electrostatics, thus opening the possibility for modulating electronic properties. This would, however, require tuning these levels to near the Fermi level, for instance, by endohedral doping of C 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Because the n = 1 peak position of epitaxial graphene is sensitive to different tip states due to poor screening in the graphene sheet, 25 it is important to keep track of the tip state. We collected the STS data for intercalation structures SiC/Na/G, SiC/Na/G/G and SLG simultaneously (i.e., with the same tip state) for use as an internal reference (in contrast to usual STS studies in which the substrate Fermi level is the most useful reference).…”
Section: Resultsmentioning
confidence: 99%
“…Different layers can be easily distinguished by the reduction in substrateinduced corrugation in the bilayer and by the systematic energy differences in IPS's in STS. 25 By choosing a lower annealing temperature (1000…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming the sample is stationary, this process indirectly probes its density of states (DOS). 27 A second interaction is also taking place, though, in which the tip bias induces an image charge in the grounded sample, resulting in an electrostatic attraction that increases with the bias. We have found that in some materials, such as graphite 28 and freestanding graphene, 29 this attraction can result in physical movement of the sample, convoluting and often eclipsing any DOS measurement.…”
Section: Methodsmentioning
confidence: 99%